Contact‐dependent suppression of CD4 T‐cell activation and proliferation by B cells activated through IgD cross‐linking. Issue 3 (March 2015) - Preciado‐Llanes, Lorena; Wing, James B.; Foster, Rachel A.; Carlring, Jennifer; Lees, Andrew; Read, Robert C.; Heath, Andrew W.
Summary Although the co‐stimulatory interaction between B and T cells is well defined, recent evidence suggests that B cells also have a regulatory role. Here, we show that B cells activated using anti‐IgD conjugated to dextran (α‐δ‐dex) directly inhibit T‐cell receptor‐induced CD4 T‐cell activation, proliferation and cytokine production. This effect was observed in CD4 T cells activated both with and without CD28 co‐stimulation. T‐cell viability was unaffected, and the T‐cell suppressive effect was mediated by contact with IgD‐activated purified B cells and not by interleukin‐10 or other soluble factors. This is the first evidence of IgD‐activated B cells mediating inhibition of activation and proliferation of CD4 T cells in humans.